Kolaborasi Mahasiswa dalam Pengabdian Masyarakat Di Desa Argapura Kecamatan Cigudeg Kabupaten Bogor - Jihan Sopyana; Mohamad Najib; Ainaya Arasya Aulia; Kurniawan; Nunik Destria Arianti; Muhamad Muslih (Jurnal Pengabdian Kepada Masyarakat Abdi Putra, 2024)
Community service is an activity that aims to help the community in several activities without expecting anything in return. Community Service Activities are one part of the Tri Dharma of Higher Education. The purpose of holding student collaboration in community service is to hone soft skills and partnerships, cross-disciplinary or scientific team collaboration (cross-competence) and student leadership in managing development programs in rural areas. Facilitating students to apply their knowledge in solving problems at the village level. Forming attitudes and feelings of love, social care, and student responsibility for the progress of society. The service targets cover several aspects, including the implementation of participation in village government, family assistance, school programs, entrepreneurship, professors' seminars, and commemoration of the Republic of Indonesia's Independence Day. During service students are taught to be critical in various matters and learn problem solving that occurs in the community. Argapura Village is a village with a lot of potential, with several programs that we have implemented to make Argapura Village even more developed.